Immune defense against S. Epidermidis biofilms: components of the extracellular polymeric substance activate distinct bactericidal mechanisms of phagocytic cells - Meyle, Eva; Brenner-Weiß, Gerald; Obst, Ursula; Prior, Birgit; Hänsch, Gertrud Maria (The international journal of artificial organs, 2012)
Bacteria, organized in biofilms, are a common cause of relapsing or persistent infections and the ultimate cause of implant-associated osteomyelitis. Bacterial biofilms initiate a prominent local inflammatory response with infiltration of polymorphonuclear neutrophils (PMN), the main protagonists of the local innate host defense against bacteria. In our previous work we found that PMN recognize and adhere to biofilms, and that phagocytosis and degranulation of bactericidal substances, such as lactoferrin, were initiated. In contrast to the situation with planktonic bacteria, opsonization of biofilms with immunoglobulin and complement was not required for PMN activation, suggesting that biofilms contain signaling components for PMN. In the present study we identified in the bacteria-free extracellular substance of Staphylococcus epidermidis biofilms protein fractions that activated PMN in vitro.